ISOLATION AND CHARACTERISATION OF ANTI-BACTERIAL RESISTANCE PATTERNS OF BACTERIAL ISOLATES FROM URINARY TRACT INFECTION IN DIABETICS - S., HARIKRISHNAN; VENNILA, ROSY; MONICA, R. (International Journal of Current Pharmaceutical Research, 2021)
Objective: Urinary tract infection (UTI) is one of the most common infections observed in diabetic patients. This study is aimed at identifying the organisms with their anti-bacterial resistance pattern. Methods: A total of 400 diabetic patients over a period of nine months presenting with symptom s of urinary tract infection were taken for the study. Their urine were cultured and an antibiogram done. Results: E. coli, Klebsiella and Enterococci were the commonest organism found. It was found that E. coli, which was the commonest organism E. Coli was sensitive to Norfloxacin and resistant to Ciprofloxacin. Conclusion: Empirical treatment with ciprofloxacin, Which is considered the drug of choice, will lead to failure of treatment.